Direct Flow Medical vs. Edwards Sapien 3 Prosthesis: A Propensity Matched Comparison on Intermediate Safety and Mortality - Edlinger, Christoph; Bannehr, Marwin; Wernly, Bernhard; Kücken, Tanja; Okamoto, Maki; Lichtenauer, Michael; Hähnel, Valentin; Reiners, David; Neuss, Michael; Butter, Christian (Frontiers in Cardiovascular Medicine, 2021)
Aims: To compare intermediate performance and mortality rates in patients, who underwent transcatheter aortic valve implantation (TAVI) with two different types of prostheses: Edwards Sapien 3 (ES3) and Direct Flow Medical (DFM). Methods and Results: 42 consecutive patients implanted with a DFM prosthesis for severe aortic stenosis were matched 1:1 with an equal number of patients, who received an ES3 during the same period. Primary endpoint was mortality. MACE, as a composite of all-cause death, stroke, and re-do-procedure (valve-in-valve), was defined as secondary endpoint. Moreover, we compared NYHA class, NT-proBNP-levels and the extent of restenosis. Patients were followed for 2 years. DFM patients showed echocardiographic elevated mean pressure gradients compared to ES3 patients before discharge (11.2 mmHg ± 5.3 vs. 3.5 mmHg ± 2.7; p < 0.001) and upon 6-months follow-up (20.3 mmHg ± 8.8 vs. 12.3 mmHg ± 4.4; p < 0.001). ES3 candidates showed superior NYHA class at follow-up (p = 0.001). Kaplan-Meier analysis revealed significantly worse survival in patients receiving a DFM prosthesis compared to ES3 (Breslow p = 0.020). MACE occurred more often in DFM patients compared to ES3 (Breslow p = 0.006). Conclusions: Patients receiving DFM valve prostheses showed worse survival and higher rates in MACE compared to ES3. Prosthesis performance regarding mean pressure gradients and patients' NYHA class also favored ES3.